Production of interleukin 1 and tumour necrosis factor activities in bronchoalveolar washings following infection of mice by influenza virus - F Vacheron; A. Rudent; S. Perin; C Labarre; Anne-Marie Quéro; M. Guenounou (1990)
Mice were infected with influenza A virus by aerosol. Bronchoalveolar washings obtained from infected mice contained interleukin 1 (IL-1) and tumour necrosis factor (TNF) activities. IL-1 was present at day 4 post-infection but not at day 7. TNF activity was present at day 4 and day 7 post-infection. The presence of both these monokines was coincident with increased cell populations in the lungs. In vitro studies demonstrated that macrophages from non-infected mice produce IL-1 and TNF activities in response to live influenza A virus stimulation. These results suggest that a direct interaction between virus and alveolar macrophages leads to IL-1 and TNF production during the course of infection and could account for both the immune responses and the pathology that occur during influenza A virus infection.